Implementation of the Social Story Method to Improve Social Interaction Skills for Hyperactive Students at Madrasah Ibtidaiyah: Implementasi Metode Social Story untuk Meningkatkan Kemampuan Interaksi Sosial pada Siswa Hiperaktif di Madrasah Ibtidaiyah - Ardiana, Richa; Nastiti, Dwi (Psikologia : Jurnal Psikologi, 2021)
This study aims to determine the implementation of the social story method to improve social interaction skills in hyperactive students at MI darusallam jogosatru. The social interaction of hyperactive children can be seen from the way students interact at school. This study uses experimental research because it influences the influence of the social story method on the social interactions of hyperactive students. The subjects in this study were hyperactive grade 5 students using a single subject design approach by observing hyperactive students and data analysis techniques using graphic analysis techniques. The result of this research is that the social story method can improve the social interaction skills of hyperactive students.